"Chinese don't walk?" – The emergence of domestic walking tourism on China's Ancient Tea Horse Road. (8th August 2021) - Witte, Alexandra
Abstract: Walking is a potential key growth area for a diversifying domestic leisure and tourism demand in China. This research discusses the emergence of walking as a touristic activity among Chinese domestic tourists on the Ancient Tea Horse Road (ATHR) in Yunnan, using mobile ethnography. Constellations of sought practices, experiences, and expressed beliefs concerning walking are discussed for four emerging communities of touristic walkers on theses trails: the hiker, the sightseer, the donkey friend and the ATHR pilgrim. The findings presented here reflect various influences from within and outside China, converging to create unique discourses around walking as a leisure pursuit. These findings have implications for the development of recreational walking opportunities in China, where officially designated destinations frequently only cater to the sightseers among walking tourists.